An analysis of the mathematical modelling of tossing a shuttlecock - Radhakrishna, V. K.; Kuralarasan, M. (International Journal of Research and Analytical Reviews, 2019)
Mathematics pervades in almost all areas of Science and even it is highly related and useful in our daily activities. Most areas of mathematics have been applied in various sports like Cricket, Football, and Tennis etc. for calculation purpose and brief analysis of the game. Here, we are modelling the toss of a shuttlecock in the sport Badminton and solving the same using mathematical formulas to calculate the time of flight, velocity, distance and height travelled by the shuttlecock.